Teaching Speaking Skills through Project-Based Learning for the Eighth Graders of Junior High School - Alfatihah Alfatihah; Devi Ismayanti; Andi Tenrisanna Syam; Rustan Santaria (Institut Agama Islam Negeri Palopo, 2022)
The objective of the study is to see whether or not project-based learning improves students’ speaking skills and their perceptions towards the implementation of PBL. The author used the quasi-experimental method. The population was 120 students. The research sample was class VIII A consisted of 16 students as an experimental group, and class VIII B consisted of 16 students as a controlled group. The instrument of the research was a speaking test and questionnaire. The author collected data through pre-tested the students, giving treatment, post-tested, and spreading questionnaires through Google form. The data were analyzed by using SPSS program version 28. The students’ result of average score in the pre-test of the experimental group was lower than the average score in the post-test (35.81 < 64.94). Meanwhile, the average score of the students in the pre-test of the controlled group was lower than the average score in post-test (41.00 < 50.75). It means that the average score of post-test in the experimental group is better than the average score of post-test in the controlled group (64.94 > 50.75). The result of the questionnaire shows the